Creating modern neuroscience the revolutionary 1950s - Shepherd, Gordon M., 1933- (New York ; Oxford : Oxford University Press, 2010)
For modern scientists, history often starts with last week's journals and is regarded as largely a quaint interest compared with the advances of today. However, this book makes the case that, measured by major advances, the greatest decade in the history of brain studies was mid-twentieth century, especially the 1950s.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Neurosciences -- History -- 20th century